Upside-Down Gods : Gregory Bateson's World of Difference - Harries-Jones, Peter (Meaning systems., 2016)
Science's conventional understanding of environment as an inert material resource underlies our unwillingness to acknowledge the military-industrial role in ongoing ecological catastrophes. In a crucial challenge to modern science's exclusive attachment to materialist premises, Bateson reframed culture, psychology, biology, and evolution in terms of feedback and communication, fundamentally altering how we perceive our relationship with nature. This intellectual biography covers the whole trajectory of Bateson's career, from his first anthropological work alongside Margaret Mead through the afterlife of his work in the development of biosemiotics. Harries-Jones shows how the sum of Bateson's thinking across numerous fields turns our notions of causality upside down, providing a moral divide between sustainable creativity and our perpetration of biocide.